Cryptocurrency adoption: current stage, opportunities, and open challenges - Al-Amri, Redhwan; Zakaria, Nur Haryani; Habbal, Adib M. Monzer; Hassan, Suhaidi (ACCENTS, 2019)
Cryptocurrency is attracting the attention of academic and non- academic researchers as an alternative architecture of currency. Because of the growing of cryptocurrency research, it is essential to value the existing research of cryptocurrency and identify potential future research areas. This paper provides an up to date review of Information system (IS) research on cryptocurrency adoption. In this paper, we conduct a systematic literature review to gather the previous research related to cryptocurrency adoption. The goal of this research is to identify the current research stage and open challenges for future studies in cryptocurrency adoption. Moreover, the paper presents a systematic literature review (SLR) of 25 research articles published on the adoption of cryptocurrency from 2014 to 2017. The results demonstrate that cryptocurrency adoption research has grown significantly throughout this period, and remains a fertile area for academic research. The results show that the cryptocurrency adoption literature can be classified according to three main classifications: qualitative research, quantitative research and others. The results of the SLR reveal that there is a lack of study focusing on the factors that are significantly influenced on the acceptance of cryptocurrency. Furthermore, there is also a lack of technology acceptance models used in addressing the issues. Research gap found is presented and discussed.